How to accompany the little prince? The interaction between spontaneous play and artistic disciplines in the use of art therapy with children - Raquel Vela González (Arteterapia)
The main goal of this article is to give significance to spontaneous play from its interaction with the arts when using art therapy with children. Starting from the observations made during the therapeutic process of a child in an art therapy workshop conducted in his school, the article concludes with the contributions of play in that specific therapeutic area and its impact on the methodological practice.